The Influence Of Hedonic And Fear Of Missing Out (Fomo) On The Interest In Buying Lapubu Dolls Among Gen Z In Bandar Lampung, Moderated By Influencers - Deny Rolind Zabara; Gema Cahyo Nuranto (MINOVa Ditria Jaya, 2025)
This study aims to analyze the influence of hedonic motivation and fear of missing out (FOMO) on the purchase interest of Labubu dolls among Gen Z in Bandar Lampung, with the moderating role of influencers. This study uses a quantitative approach and survey method to collect data.The sample in this study was 120 respondents. The analysis tool usedand the data to be analyzed statistically using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method using Smart PLS software.0.The results of the study show that hedonic motivation has a positive and significant effect on purchase intention, while FOMO does not show a significant effect. In addition, influencers failed to moderate the influence of both on purchase intention. These findings provide important insights for entrepreneurs in designing the right marketing strategies to attract Gen Z purchase interest and highlight the importance of understanding the psychological factors that influence their purchasing decisions.